Longitudinal Strain and Strain Rate in Patients With Hemodynamically Significant Ventricular Septal Defects. (April 2014) - Penk, Jamie; Patel, Angira; Lay, Amy; Webb, Catherine
Background: Patients with significant overcirculation from large ventricular septal defects (VSDs) may have altered contractility compared to normal patients. Methods: Patients were enrolled prospectively. Patients were excluded if they were acutely ill or over age five. Left ventricular longitudinal strain and strain rate were measured in patients with VSDs referred for surgical correction and control participants with structurally normal hearts. Results: There was no difference in the average longitudinal strain or strain rate of six segments in the left ventricle. The mean for both the groups was 19.9% ( P = .95). Strain rate was 1.5 s −1 in the patients with a VSD and 1.42 s −1 in the control group ( P = .30). The left ventricular end diastolic dimension was significantly larger in the group with ventricular defects (z score 1.38 vs −0.37) than the control group ( P = .000). Conclusions: The left ventricle end-diastolic dimension in patients with ventricular defects was significantly larger, but there was no difference in longitudinal strain or strain rate.